Effect of L‐cysteine on the rheology and baking quality of doughs formulated with flour from five contrasting Canada spring wheat cultivars. Issue 2 (1st December 2019) - Tozatti, Patricia; Fleitas, María Constanza; Briggs, Connie; Hucl, Pierre; Chibbar, Ravindra N.; Nickerson, Michael T.
Abstract: Background and Objectives: Wheat grain quality parameters are influenced by the composition of gluten proteins. To overcome wheat grain quality limitations, dough improvers such as reducing agents can be added to reduce mixing time and improve dough extensibility. The overall objective of this research was to examine the effect of L‐cysteine (L‐cys) concentration on the rheology and baking quality of doughs prepared using five western Canadian spring wheat cultivars. Findings: The addition of L‐cys resulted in a significant ( p  < .05) decrease in dough strength and handling properties, where stronger gluten strength wheats were less affected by addition and had improved dough handling properties, loaf volume, and softer crumb structure. Conclusions: The addition of L‐cys to wheat flours reduced mixing time up to 47%, increased loaf volume (up to 9%), and elasticity of the products, those characteristics are desired to increase the efficiency of the automated processes for bread products. Significance and novelty: The optimization of time versus quality of bread is crucial for the industry. Therefore, reducing agents can be used in stronger wheat cultivars as means to improve efficiency of production (i.e., lower mixing time) and result in equal or higher quality bread loaf (i.e., loaf volume).